A cross-industry assessment of the flow rate-elapsed time profiles of test equipment typically used for dry-powder inhaler (DPI) testing: Part 2– analysis of transient air flow in the testing of DPIs with compendial cascade impactors. Issue 12 (11th August 2020) - Versteeg, H. K.; Roberts, D. L.; Chambers, F.; Cooper, A.; Copley, M.; Mitchell, J. P.; Mohammed, H.
Abstract: We describe a computational model that captures the physics of the unsteady air-flow startup that accompanies the testing of dry-powder inhalers (DPI) with cascade impactors (CIs) specifically when following methods described in the pharmacopeial compendia. This transient has been measured in a multi-organization study for a wide range of conditions and reported in a companion article. The DPI test system is simulated as a series of flow resistances, starting with the inhaler itself, including each stage of the CI, and finishing with the prescribed flow control valve, wherein the flow is held at sonic velocity. The resulting non-dimensional equations indicate the relative importance of the several flow resistances. The model agrees well with the available experimental data for the Next Generation Impactor (NGI™) and qualitatively with the available data from a variety of the configurations of the Andersen 8-stage cascade impactor (ACI), including the typical 4-kPa pressure drop across an entry fixed orifice mimicking surrogate low-, medium- and high-resistance DPIs. The model indicates that the startup times for the NGI and for the ACI are very reasonably estimated by a simple "reference time, " given in Equation (26) and, for an inlet flow rate of 60 L/min, having a value of 277 ms and 113 ms for the NGI and ACI (60-L/min configuration), respectively. The model also enables a baseline, universal design curve for the flow rise-time performance of testing DPIs with the NGI (Figures 9a and b), because this impactor requires no change of components for any inlet flow rate. Copyright © 2020 American Association for Aerosol Research